2023
DOI: 10.2174/1566524022666220427102048
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Signatures in Colorectal Cancer Progression

Abstract: Aims: Due to a large number of identified hub-genes, encoding key molecular regulators, which involve in signal transduction and metabolic pathways in cancers, it is relevant to systemize and update these findings. Background: Colorectal cancer (CRC) is the third leading cause of cancer death in the world with high metastatic potential. Elucidating the pathogenic mechanisms and selection of novel biomarkers in CRC is of great clinical significance. Objective: This analytical review aims at systematization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…Liu et al 77 used analysis of the TCGA database revealed that the expression of GUCA2A and GUCA2B was significantly downregulated in CRC tissues, which is consistent with our results. As reported by Ershov et al 78 the expression of GUCA2A was considerably downregulated in CRC tissues, which is consistent with our findings. According to Xu et al 79 , GUCA2A expression level in colorectal cancer tissues were lower than in healthy tissues, which is consistent with the experimental findings from our investigations.…”
Section: Discussionsupporting
confidence: 94%
“…Liu et al 77 used analysis of the TCGA database revealed that the expression of GUCA2A and GUCA2B was significantly downregulated in CRC tissues, which is consistent with our results. As reported by Ershov et al 78 the expression of GUCA2A was considerably downregulated in CRC tissues, which is consistent with our findings. According to Xu et al 79 , GUCA2A expression level in colorectal cancer tissues were lower than in healthy tissues, which is consistent with the experimental findings from our investigations.…”
Section: Discussionsupporting
confidence: 94%
“…In the remodeling steps during tumor growth, the normal ECM collagens are substituted with a tumor-specific collagen profile [ 70 ]. Increased expression of different collagens was associated with tumor progression and a poor prognosis in various types of epithelial cancers including colorectal [ 71 ], esophagus [ 72 ], glioma [ 73 ], gastric [ 74 , 75 ], head and neck [ 76 ], lung [ 77 ], ovarian [ 78 ], pancreatic [ 79 ], renal [ 80 ], breast [ 81 , 82 ], and cervical cancer [ 83 ]. The profile of different collagen types expressed in various solid cancers is presented as a heatmap in Figure 2 .…”
Section: Collagen Family and Cancermentioning
confidence: 99%
“…This protein is present in many fibrotic illnesses included multiple organs, such as heart, lung fibrosis, kidney and liver [ [25] , [26] , [27] ]. Collagen III contributes to cell adhesion, motility, and differentiation through its interaction with integrins [ 28 ] THBS2 is associated with metastatic colorectal cancer, is shown to be expressed at higher levels in lung cancer, and participates in focal adhesion signalling pathways [ [29] , [30] ]. CCND1 gene regulates cell cycle progression and its upregulation promotes the development of various tumours.…”
Section: Discussionmentioning
confidence: 99%